A Multidisciplinary Perspective of Ultra-Processed Foods and Associated Food Processing Technologies: A View of the Sustainable Road Ahead - Francesco Capozzi (MDPI AG, 2021)
Ultra-processed foods (UPFs) are negatively perceived by part of the scientific community, the public, and policymakers alike, to the extent they are sometimes referred to as not “real food”. Many observational surveys have linked consumption of UPFs to adverse health outcomes. This narrative synthesis and scientific reappraisal of available evidence aims to: (i) critically evaluate UPF-related scientific literature on diet and disease and identify possible research gaps or biases in the interpretation of data; (ii) emphasize the innovative potential of various processing technologies that can lead to modifications of the food matrix with beneficial health effects; (iii) highlight the possible links between processing, sustainability and circular economy through the valorisation of by-products; and (iv) delineate the conceptual parameters of new paradigms in food evaluation and classification systems. Although greater consumption of UPFs has been associated with obesity, unfavorable cardiometabolic risk factor profiles, and increased risk for non-communicable diseases, whether specific food processing techniques leading to ultra-processed formulations are responsible for the observed links between UPFs and various health outcomes remains elusive and far from being understood. Evolving technologies can be used in the context of sustainable valorisation of food processing by-products to create novel, low-cost UPFs with improved nutritional value and health potential. New paradigms of food evaluation and assessment should be funded and developed on several novel pillars—enginomics, signalling, and precision nutrition—taking advantage of available digital technologies and artificial intelligence. Research is needed to generate required scientific knowledge to either expand the current or create new food evaluation and classification systems, incorporating processing aspects that may have a significant impact on health and wellness, together with factors related to the personalization of foods and diets, while not neglecting recycling and sustainability aspects. The complexity and the predicted immense size of these tasks calls for open innovation mentality and a new mindset promoting multidisciplinary collaborations and partnerships between academia and industry.